Neoliberalism, Biocommunicability and the Production of Healthy and Unhealthy Citizens. An Analysis of Policies to combat Anemia seen from the Peruvian Amazon. - Palma, Helen (2020)
Based on an ethnographic study among a multi-ethnic society of the Peruvian Amazon composed primarily of Awajún and Wampis, a critical reflection is made of the biocommunicability processes associated with policies to combat anemia. The analysis highlights the insertion of these processes in a pre-existing web of inter- and intra-ethnic tensions. Careful and prolonged accompaniment of these processes enabled the identification of ideological and moral aspects expressed in a medicalizing vision of anemia, as well as the reproduction of a notion of citizenship based on the productivity, individualism and functionalism of neoliberal logic. Thus, we hope to contribute to the analysis of official health policies for indigenous populations, relevant at a time when there is a clear demand for an intercultural approach and a necessity to be attentive to possible processes of medicalization of indigenous health.